INDIKATOR PARTISIPASI MASYARAKAT DALAM SISTEM TRANSPORTASI BERKELANJUTAN - Herman, Herman (Jurnal Transportasi, 2011)
Sustainable transport system should be able to provide physical access to places of employment, health, education, recreation, and other places associated with human life. In addition, sustainable transport must also support the economic growth and poverty reduction. The purpose of this study is to identify the forms of community participation and develop indicators of community participation in a transportation. A comparison of transport systems in two cities in Indonesia, namely Semarang and Surabaya, is selected as a case study. The results indicate that the forms of community participation in sustainable transportation system include payments of fuel tax, vehicle tax, parking charges, public transport tickets, and road pricing.In addition, there are many indicators that can be used to assess the sustainability of an urban transport system. The results also show that the transport system in Surabaya is better than that found in Semarang.Keywords: sustainable transport system, transportation system indicators, community participation.